Association of Diabetes and Hypertension With Brain Structural Integrity and Cognition in the Boston Puerto Rican Health Study Cohort. (12th April 2022) - Guan, Yi; Ebrahimzadeh, Seyed Amir; Cheng, Chia-hsin; Chen, Weifan; Leung, Tiffany; Bigornia, Sherman; Palacios, Natalia; Garelnabi, Mahdi O.; Scott, Tammy; Bhadelia, Rafeeque; Tucker, Katherine L.; Koo, Bang-Bon; et al.
Abstract : Background and Objectives: The Boston Puerto Rican Health Study (BPRHS) is a longitudinal study following self-identified Puerto Rican older adults living in the Greater Boston area. Studies have shown higher prevalence of hypertension (HTN) and type 2 diabetes (T2D) within this ethnic group compared to age-matched non-Hispanic White adults. In this study, we investigated the associations of HTN and T2D comorbidity on brain structural integrity and cognitive capacity in community-dwelling Puerto Rican adults and compared these measures with older adult participants (non-Hispanic White and Hispanic) from the Alzheimer's Disease Neuroimaging Initiative (ADNI) and National Alzheimer's Coordinating Center (NACC) databases. Methods: BPRHS participants who underwent brain MRI and cognitive testing were divided into 4 groups based on their HTN and T2D status: HTN−/T2D−, HTN+/T2D−, HTN−/T2D+, and HTN+/T2D+. We assessed microstructural integrity of white matter (WM) pathways using diffusion MRI, brain macrostructural integrity using hippocampal volumes, and brain age using T1-weighted MRI and cognitive test scores. BPRHS results were then compared with results from non-Hispanic White and Hispanic participants from the ADNI and NACC databases. Results: The prevalence of HTN was almost 2 times (66.7% vs 38.7%) and of T2D was 5 times (31.8% vs 6.6.%) higher in BPRHS than in ADNI non-Hispanic White participants. Diffusion MRI showed clear deterioration patterns in major WM tracts in the HTN+/T2D+ group and, to a lesser extent, in the HTN+/T2D− group compared to the HTN−/T2D− group. HTN+/T2D+ participants also had the smallest hippocampal volume and larger brain aging deviations. Trends toward lower executive function and global cognitive scores were observed in HTN+/T2D+ relative to HTN−/T2D− individuals. MRI measures and the Mini-Mental State Examination (MMSE) scores from the HTN+/T2D+ BPRHS group resembled those of ADNI White participants with progressive mild cognitive impairment (MCI), while the BPRHS HTN−/T2D− participants resembled participants with stable MCI. The BPRHS was not significantly different from the ADNI + NACC Hispanic cohort on imaging or MMSE measures. Discussion: The effects of T2D and HTN comorbidity led to greater brain structural disruptions than HTN alone. The high prevalence of HTN and T2D in the Puerto Rican population may be a key factor contributing to health disparities in cognitive impairment in this group compared to non-Hispanic White adults in the same age range. Trial Registration Information: ClinicalTrials.gov identifier: NCT01231958.